Non‐Chemotherapy‐Induced Agranulocytosis Detected by a Prospective Pharmacovigilance Program in a Tertiary Hospital. Issue 6 (11th June 2015) - Medrano‐Casique, Nicolás; Tong, Hoi Y.; Borobia, Alberto M.; Carcas, Antonio J.; Frías, Jesús; Ramírez, Elena
Abstract: We conducted a prospective evaluation of non‐chemotherapy‐induced agranulocytosis (NIA) in a tertiary hospital in Spain. Through our Prospective Pharmacovigilance Program from Laboratory Signals at Hospital, we detected agranulocytosis cases over a period of 42 consecutive months. This report estimates incidence, drug causality, clinical features and outcomes of NIA cases and assesses laboratory differences with respect to non‐NIA. We detected 1349 cases of agranulocytosis in 538 adult patients; of these, 43 cases in 40 patients were caused by non‐chemotherapy drugs. The incidence rate for 10, 000 patients during the study period was 2.75 [Poisson confidence interval (CI)‐95%: 0.62–7.22]. The mean (S.D.) age was 48 (21) years. All cases were categorized as serious, because they required hospitalization (28 cases) or prolongation of hospitalization (15 cases). The outcome was recovery without sequela (39 cases), recovery with sequela (one case of toe amputation) or death (three cases, 7%). The most frequent cause of NIA was antimicrobial drugs (19 cases). The highest incidence rate per 10, 000 defined daily doses was for cefepime (83.85; Poisson‐CI 95%: 67–102.89). Automatic linear modelling (n = 75, R 2  = 77.9%) showed a significant inverse association with platelets, alkaline phosphatase, C‐reactive protein, fibrinogen, lactate dehydrogenase; and direct association with mean corpuscular haemoglobin, and haematocrit. A generalized linear model retained platelets, total serum proteins, creatinine and haemoglobin. The findings suggest an immune‐mediated destruction or myeloid toxicity, possibly facilitated by an increase in drug exposure. There might be additional contributing factors, such as nutritional deficiencies or chronic diseases, to develop NIA after exposure to a potentially causative drug.